Key Predictors of Quality of Life Among the Elderly in Kampar regency: A Multidimensional Approach - Indrawati; Gusman Virgo; Putri Eka Sudiarti (Postgraduate, University of Mataram, 2025)
This research investigates many factors that affect the quality of life of the elderly in Kampar Regency, Riau. This research, with 402 people aged 60 and above, indicated that the elderly's perception of their own health is the most significant predictor of their overall health-related quality of life. Social support—assistance from family, friends, and the community has been shown to be very impactful, highlighting the significance of social connections for well-being in later life. Leisure activities —spanning from morning walks to engaging in religious practices or gardening—substantially enhance well-being. Interestingly, the elderly's perception of justice in healthcare services also affects their quality of life. Elderly individuals who feel that access to healthcare services is distributed fairly tend to have a better quality of life. Meanwhile, aging does show negative effects, but this emphasizes the importance of programs that specifically target the needs of the elderly across various age groups, especially the very elderly. The utilization of community-based care services also plays an important role in improving the quality of life, demonstrating the value of a local support system that is easily accessible to the elderly. These findings provide a comprehensive picture of what is truly important for the elderly in Kampar Regency, and can serve as a foundation for the development of more effective programs to enhance well-being in old age.